Planning the Food Estate for Community Development and Welfare - LUBIS, Maksum Syahri; MUNAWIR, Zaini; MATONDANG, Saiful Anwar (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.12.5(53).11, 2021)
Regional Planning prepares the development program for community welfare in future. This planning research focuses on the Food Estate development of North Sumatera Province of Indonesia. A food Estate of North Sumatera puts forward the agricultural sector as the fundamental element for the industry and services. Data obtained found that both the Central and local governments in North Sumatera already launched a food estate of around 61,042 hectares, covering four Regencies; namely, Humbang Hasundutan, Pakpak Barat, Tapanuli Tengah and Tapanuli Utara. The Ministry of Environment and Forestry also launched a 1,150-hectare botanical garden and a 500-hectare herbal science park. It concludes that the Regional Planning for sustainable agriculture prioritises the management of agricultural ecosystems covers biodiversity with the empowerment strategies supported by both the Central Government of Indonesia and local ones. Such Regional Planning increases community development and future welfare.